1999
DOI: 10.1111/j.2042-3306.1999.tb03801.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of equine motor neuron disease

Abstract: Summary The characteristics of the ocular manifestations of equine motor neuron disease (EMND) are described. Forty‐two horses with histories, clinical signs and necropsies compatible with EMND were the subjects of this study. Ophthalmoscopic lesions that varied in severity were found in 40 of 42 horses and appeared as a distinct pigmented reticulated pattern at the tapetal‐nontapetal junction or throughout the fundus, depending upon severity. The pattern colours ranged from yellow brown to black. Areas of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Other evidence of hypovitaminosis E was found on direct and indirect ophthalmoscopic examination; affected horses reveal a pigmentary retinopathy which involves the retinal pigment epithelium. While the vision of affected horses appears normal, there are changes in the electroretinogram [13,17]. Furthermore, electron microscopic studies on the spinal cords of EMND animals have consistently demonstrated the presence of large endothelial accumulations of lipopigment granules [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence of hypovitaminosis E was found on direct and indirect ophthalmoscopic examination; affected horses reveal a pigmentary retinopathy which involves the retinal pigment epithelium. While the vision of affected horses appears normal, there are changes in the electroretinogram [13,17]. Furthermore, electron microscopic studies on the spinal cords of EMND animals have consistently demonstrated the presence of large endothelial accumulations of lipopigment granules [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fundic examination may reveal a mosaic pattern of dark yellow to dark brown lipofuschin deposits in the tapetum and at the tapetal-nontapetal junction (Riis et al 1999). Consequently, horses with EMND are unable to lock their passive stay apparatus, and appear weaker when standing than when moving.…”
Section: Clinical Signsmentioning
confidence: 99%
“…29 Massive accumulations of lipofuscin were found in the pigmented epithelium of rats lacking various antioxidants including vitamin E 49 ; such deposits are thought to be the end products of peroxidation of membrane polyunsaturated fatty acids. 50 Low blood and spinal cord vitamin E concentrations have consistently been found in horses with EMND in the United States and an epidemiologic study linked low serum vitamin E to EMND risk (see Epidemiology section). The typical history for EMND cases also includes lack of access to green forage, so vitamin E deficiency is thought to be involved in the pathogenesis of the disease.…”
Section: History and Epidemiologymentioning
confidence: 99%
“…57 In some 40% of cases, fundoscopic examination reveals a horizontal band of pigment above the optic disc at the tapetal-nontapetal junction ( Figure 19.6). 40,50 The pigment may be brown-black to yellow-brown and has a reticulated or mosaic appearance. Surprisingly, problems with vision have not been reported even in EMND horses with severe pigment retinopathy.…”
Section: Clinical Signsmentioning
confidence: 99%